Self and identity of emergency nurses who pursue higher education in Ireland - Greene, Catherine Jane (Trinity College Dublin. School of Education. Discipline of Education, 2022)
Higher education is a significant feature of contemporary nursing practice. The nursing profession has witnessed significant professional, political, and educational reform over recent years, both nationally and internationally. These reforms have been largely in response to changes in the broader healthcare and economic landscape. Additionally, working in increasingly complex and varied environments, coupled with changing patterns of health and illness, requires that nurses are appropriately educated. While nurses have found themselves with limited opportunities over recent years, irrespective of educational attainment, orientation to higher education has been consistent, particularly among emergency nurses in Ireland. Interestingly, there is no requirement by the professional regulatory authority in Ireland for registered nurses to participate in educational activities in order to maintain professional registration. While the literature has broadly considered decision-making strategies and experiences among the general nursing population, no study has explored these factors among emergency nurses. This study employed a narrative inquiry approach to explore the influences, decision-making, and experiences of emergency nurses who have pursued higher education and took the theoretical stance that these areas could not be fully understood without being illuminated by the concepts of self and identity. This thesis supports the well-established claims of promotional and educational opportunities, and patient care outcomes as reasons for pursuing higher education. While these have been credible driving forces in the uptake of higher education, this study also demonstrates that emergency nurses' personal mandates in terms of self and identity are more influential and enduring in the decision to participate in higher educational activities. It is envisaged that the results of this research will be important in the understanding of why and when emergency nurses engage in higher education, thus leading to a greater knowledge of how higher educational opportunities can be focused for this group of nursing professionals.
APPROVED
Keywords: Emergency nurses; Higher education; Self; Identity; Professional identity; Ireland